URIC ACID LEVELS IN PULMONARY TUBERCULOSIS PATIENTS DURING ANTI-TUBERCULOSIS THERAPY AT SEKIP PUBLIC HEALTH CENTER PALEMBANG IN 2025 - Tri Oktavia; Juwy Trianes; Dhea Wulandari (Quality: Jurnal Kesehatan, 2026)
Tuberculosis or TB is an infectious disease caused by the bacterium Mycobacterium tuberculosis. One of the Anti-Tuberculosis Drugs (OAT) is Rifampicin, Isoniazid (INH), Pirazinamid, and Ethambutol. Pirazinamid, and Ethambutol are types of OATs that are able to increase acid levels but their use for a long time can pose some risk of side effects in patients such as impaired liver function. Gout is a normal compound in the final stages of purine metabolism in the body. The purpose of this study is to find out the description of uric acid levels in patients with pulmonary tuberculosis who consume anti-tuberculosis drugs based on gender, age, and length of time consuming tuberculosis drugs at the Sekip Palembang Health Center in 2025. This study is a descriptive research, with a sample of 31 samples using the total sampling technique. The examination was carried out using the Point Of Care Testing (POCT) method. The results of the study of 31 people with tuberculosis who consumed OAT as many as 18 people (58%) had high uric acid levels. Based on male gender, 12 people (57%) had high uric acid levels. Meanwhile, 6 people (60%) had high uric acid levels. Based on the age of the adolescent group of 1 person (100%) high uric acid levels, the adult group of 8 people (67%) of high uric acid levels, the middle-aged youth group of 4 people (36%) of high uric acid levels, then the old adult group of 5 people (71%) of high uric acid levels. Based on the length of time of consuming anti-tuberculosis drugs in the early phase of treatment, 14 people (93%) had high uric acid levels. Meanwhile, the advanced phase treatment was 4 people (25%) with high uric acid levels. Recommended to pulmonary tuberculosis patients who consume OAT to reduce the consumption of foods high in purine and regularly check uric acid levels during treatment.